Silencing of PDC-E1β genes affects chloroplast development and amino acid metabolism in tobacco - Li, Dingjie; Xia, Kaitong; Zhang, Hui; Li, Zunqiang; Xie, Xiaodong; Zhou, Huina; Zhai, Niu; Xu, Guoyun (Industrial crops and products, 2025)
Chloroplasts, essential to the photosynthetic process, are pivotal in orchestrating the development and growth of plants. The pyruvate dehydrogenase complex (PDC) serves as a link between the citric acid cycle and glycolysis, supplying energy and carbon skeletons vital for plant metabolism. However, the involvement of the PDC in chloroplast development is not yet fully elucidated. Here, we provide evidence for the role of the PDC E1 component β subunit (PDC-E1β) in tobacco (Nicotiana tabacum L.) chloroplast development and amino acid metabolism. Transgenic tobacco plants with RNA interference (RNAi) targeting four PDC-E1β genes displayed a pale-green variegated leaf phenotype. The phenotype exhibited decreased chlorophyll and defective chloroplast development. Transcriptome and metabolome analyses revealed significant alterations in genes and metabolites related to photosynthesis, amino acid metabolism, and chlorophyll biosynthesis. Silencing of PDC-E1β genes downregulated PEP-dependent chloroplast gene expression and chloroplast protein levels. Moreover, silencing of PDC-E1β genes disrupted amino acid metabolism, with the variegated phenotype partially reversible by exogenous tryptophan supplementation. Our findings elucidate the significance of PDC-E1β in chloroplast development and the interconnected metabolic pathways that regulate plant organelle function. This research provides novel perspectives on the intricate mechanisms governing chloroplast development and the metabolic pathways that sustain it. •PDC-E1β silencing in tobacco results in variegated leaves.•Disruption of PDC-E1β genes affect photosynthesis and amino acid metabolism.•Tryptophan supplementation partially rescues the variegated leaf phenotype.